The Ineffectiveness of Consumer Legal Protection in Overcoming Irregularities in Our Oil Distribution in Indonesia - Kadek Julia Mahadewi; Rafika Amalia; Tania Novelin (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to analyze the gap between consumer protection regulations and the irregular practices of Minyak Kita distribution in Indonesia, as well as examine the legal liability of business actors and the state from a civil law perspective. This study uses normative legal methods with legislative, conceptual, and case approaches, and is analyzed qualitatively. The results of the study show that normatively, Law Number 8 of 1999 concerning Consumer Protection has provided a strong legal basis in protecting consumer rights. However, in practice, there are still various irregularities in the distribution of Minyak Kita, such as volume reduction, smuggling, hoarding, and sales above the highest retail price. This shows that there is a gap between law as a norm (das sollen) and reality (das sein). From a civil perspective, business actors can be held accountable based on the principles of unlawful acts and strict liability. However, these mechanisms have not been effective due to limited consumer access to legal remedies and low legal awareness. On the other hand, the state as a regulator and supervisor has also not carried out its functions optimally in supervising distribution and enforcing the law. Thus, consumer protection in the case of Minyak Kita is still formalistic and has not provided substantive protection. It is necessary to strengthen law enforcement, distribution supervision, and consumer empowerment so that the consumer protection system can run effectively.